Technique To Enhance The Bandwidth Of A Very Thin Artificial Magnetic Condutor (AMC) - Md Ali, Siti Adlina; Abu, Maisarah; Zabri @ Suhaimi, Siti Normi; Anas, Siti Aisyah; Aziziuddin, N (Penerbit UniMAP, 2020)
This paper introduces a technique to enhance the bandwidth of the Artificial Magnetic Conductor (AMC). A multilayer patch type of Frequency Selective Surface (FSS) is stacked on the AMC structure, to increase the thickness of the overall structure contributing to the lower inductivity consequently the higher the bandwidth. Both AMC and FSS structures were designed by using Rogers RT5880 with the thickness of 0.254 mm and permittivity of 2.2. The bandwidth of the AMC structure is successfully enhanced from 1.97% to 3.79%. The AMC was designed at 12 GHz which can be applied for 5G applications.